Jehoiachin and his oracle: a Jeremianic scribal framework for the end of the Deuteronomistic history - Sensenig, Melvin L. (Perspectives on Hebrew Scriptures and its Contexts, 2020)
Frontmatter -- TABLE OF CONTENTS -- FOREWORD -- ACKNOWLEDGMENTS -- LIST OF ABBREVIATIONS -- INTRODUCTION -- CHAPTER 1. A HISTORY – AND THEOLOGY – OF SCHOLARSHIP -- CHAPTER 2. THE ORACLE IN CANONICAL CONTEXT -- CHAPTER 3. JEHOIACHIN’S ORACLE AND THE ORACLES AGAINST THE NATIONS -- CHAPTER 4. A HOPE AND A FUTURE FOR JEHOIACHIN? -- CONCLUSION: A NEW CRITICAL FRAMEWORK FOR JEHOIACHIN AND HIS ORACLE -- APPENDICES -- REFERENCES CITED -- INDICES